Life threatening hypokalaemia during treatment of severe diltiazem overdose with high dose insulin euglycemic therapy: a case report. Issue 1 (30th November 2021) - Kozman, Andrew; Hoggett, Kerry; Soderstrom, Jessamine
Abstract: Calcium channel blockers (CCB) overdose can result in cardiogenic shock and that high dose insulin euglycaemic therapy (HIET) is increasingly used to treat CCB poisoning. This case illustrates the risk of severe hypokalaemia resulting from HIET for calcium channel blocker poisoning.